The integrated stress response. (14th September 2016) - Pakos‐Zebrucka, Karolina; Koryga, Izabela; Mnich, Katarzyna; Ljujic, Mila; Samali, Afshin; Gorman, Adrienne M
Abstract: In response to diverse stress stimuli, eukaryotic cells activate a common adaptive pathway, termed the integrated stress response (ISR), to restore cellular homeostasis. The core event in this pathway is the phosphorylation of eukaryotic translation initiation factor 2 alpha (eIF2α) by one of four members of the eIF2α kinase family, which leads to a decrease in global protein synthesis and the induction of selected genes, including the transcription factor ATF4, that together promote cellular recovery. The gene expression program activated by the ISR optimizes the cellular response to stress and is dependent on the cellular context, as well as on the nature and intensity of the stress stimuli. Although the ISR is primarily a pro‐survival, homeostatic program, exposure to severe stress can drive signaling toward cell death. Here, we review current understanding of the ISR signaling and how it regulates cell fate under diverse types of stress. Abstract : In order to restore cellular homeostasis, stress stimuli activate a common adaptive pathway termed the integrated stress response (ISR). This review highlights the current understanding of ISR pathways and how these regulate cell fate under diverse stress conditions.